Exploring crystal methamphetamine use among school-going learners: a qualitative case study in South African schools - Singwane, Thembinkosi Peter; Ramoshaba, Dillo Justin (Penerbit Universiti Kebangsaan Malaysia, 2024)
The increasing prevalence of drug use in schools poses significant challenges for educational environments and society at large. Persistent substance abuse among students is linked to various negative outcomes, including poor academic performance, strained relationships, physical injuries, violence, heightened sexual activity, and suicidal ideation. This qualitative study employed a multiple case study design to investigate crystal methamphetamine use among community members and learners in selected schools in Polokwane, South Africa. Data were collected through semi-structured interviews, which provided rich insights into the experiences of school-going learners regarding crystal meth use. The findings reveal that learners who engage in crystal meth use experience considerable declines in both physical and mental health. Many participants reported noticeable physical changes, such as significant weight loss. Additionally, the study identified adverse behavioural changes among these learners; they often exhibited disruptive behaviour and a lack of respect towards teachers, further complicating classroom dynamics. These results underscore the urgent need for targeted interventions to address substance abuse in educational settings and promote healthier behaviours among students.